Comparison of the PU.1 transcriptional regulome and interactome in human and mouse inflammatory dendritic cells. Issue 4 (2nd December 2020) - Scheenstra, Maaike R.; Martínez‐Botía, Patricia; Acebes‐Huerta, Andrea; Brouwer, Rutger W.W.; Caballero‐Sánchez, Noemí; Gillemans, Nynke; De Bleser, Pieter; Nota, Benjamin; De Cuyper, Iris M.; Salunkhe, Vishal; Woltman, Andrea M.; van de Laar, Lianne; et al.
Abstract: Dendritic cells (DCs) are key immune modulators and are able to mount immune responses or tolerance. DC differentiation and activation imply a plethora of molecular and cellular responses, including transcriptional changes. PU.1 is a highly expressed transcription factor in DCs and coordinates relevant aspects of DC biology. Due to their role as immune regulators, DCs pose as a promising immunotherapy tool. However, some of their functional features, such as survival, activation, or migration, are compromised due to the limitations to simulate in vitro the physiologic DC differentiation process. A better knowledge of transcriptional programs would allow the identification of potential targets for manipulation with the aim of obtaining "qualified" DCs for immunotherapy purposes. Most of the current knowledge regarding DC biology derives from studies using mouse models, which not always find a parallel in human. In the present study, we dissect the PU.1 transcriptional regulome and interactome in mouse and human DCs, in the steady state or LPS activated. The PU.1 transcriptional regulome was identified by performing PU.1 chromatin immunoprecipitation followed by high‐throughput sequencing and pairing these data with RNAsequencing data. The PU.1 interactome was identified by performing PU.1 immunoprecipitation followed by mass spectrometry analysis. Our results portray PU.1 as a pivotal factor that plays an important role in the regulation of genes required for proper DC activation and function, and assures the repression of nonlineage genes. The interspecies differences between human and mouse DCs are surprisingly substantial, highlighting the need to study the biology of human DCs. Graphical Abstract: Comparing human and mouse PU.1 regulome and interactome in inflammatory DCs reveals species‐specific responses and conserved regulatory features of PU.1.